In-situ non-contact 3D optical deformation measurement of large capacity composite tank based on close-range photogrammetry. (August 2019) - Goda, Ibrahim; L'Hostis, Gildas; Guerlain, Philippe
Highlights: A non-contact 3D optical static deformation measurement system, based on photogrammetric detection has been applied to experimentally evaluate the structural properties of large-capacity composite tank. The photogrammetry technique allows an accurate reconstruction of the 3D shape of the tank from a number of freehand digital pictures taken from different angles and positions. The composite tank is subjected to different internal loading tests including hydrostatic pressure and water-pressurizing test. The obtained results are information rich, reliable and provided in different locations on tank surface, enabling detailed 3D deformation analysis of the composite tank. Abstract: Recently, fiber-reinforced composites are widely used in manufacturing of large storage tanks for transportation purposes, thanks to their excellent mechanical and chemical performance, and their good applicability to the shaping of particular geometries. In this contribution, a non-contact 3D optical deformation measurement technique is proposed for monitoring the deformation of carbon-fiber reinforced composite tank subjected to different loading scenarios, which could not be achieved by traditional displacement sensors and resistance strain gauges due to large measuring ranges. This technique is based on the close-range photogrammetry technology, wherein 3D information is extracted from two-dimensional photographs. This is done by positioning artificial reference point markers on the measuring tank before loading, and calculate the 3D coordinates of these markers through analyzing the group photos captured in each loading stage. By tracking and comparing the 3D coordinates of the point markers among different loading stages, the 3D deformation of the tank is obtained. The loading tests comprise both hydrostatic pressure and water-pressurizing tests. The performed in-situ measurements show that the proposed technique can fulfill the efficiency and accuracy requirement of deformation measurement in tank loading tests. This in turn significantly contributes to better understanding the mechanical response at the macroscopic scale, thus improving safety performance.